PENGARUH KEPERCAYAAN MEREK PADA LOYALITAS PENGGUNA KARTU IM3 DI YOGYAKARTA - , AKHIR JEKSON M; , Sudiyanti, S.E., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is backgrounded by the tighter competition among cellular operators in Indonesia. Each operator competes in keeping its customers or even in winning new ones. In particular, this research reviews about Indosat IM3 brand trust measured by several factors such as brand predictability, brand reputation, brand competency, company trust, and preference which are forming factors of brand loyalty. This research is purposed to test the significant effect of brand predictability factor, brand reputation, brand competition, company trust, and brand preference on Indosat IM3 brand loyalty. Respondents involved in this research are 122 respondents. Method used is Non Probability Sampling and samples decided with combination of Sampling Convenience Method and Purposive Sampling Method. Data collection was done by distributing questionnaires to respondents. Data analysis method is done with Double Linear Regression and Simple Linear Regression in which the data is formerly processed using software SPSS 17 for Windows. The test result of Double Linear Regression shows that there is significant effect of brand predictability on trust in brand with significancy value of 0.001. There is significant effect of brand reputation variable on trust in brand with significancy value of 0.013. There is also significant effect of brand competence on trust in brand with significancy value of 0.000. Significant effect of trust in company on trust in brand is as much as 0.000. There is significant effect of brand liking on trust in brand as much as 0.000. Meanwhile, in simple regression test which is testing the effect of trust in brand variable on brand loyalty. There is significant effect of trust in brand on brand loyalty as much as 0.000.